Timely Venous Thromboembolism Prophylaxis in Trauma: A Team Approach to Process Improvement. Issue 3 (May 2020) - Farrell, Loretta; Romeo, Oreste; Johnson, Ruth
Abstract : Venous thromboembolism is a significant complication in trauma. Multisystem injury, advancing age, surgery, and blood transfusion all contribute to the risk of venous thromboembolism in trauma patients. Our Level I trauma center was identified as an outlier with compliance in timely venous thromboembolism prophylaxis in the Michigan Trauma Quality Improvement Program, a statewide collaborative for improving trauma care. The purpose of this study was to provide an evaluation of a performance improvement project to increase the timely administration of venous thromboembolism prophylaxis in admitted trauma patients. Using a Plan-Do-Study-Act method of quality improvement, we initiated a focused, goal-directed team approach that emphasized education, tracking, and feedback. This approach resulted in improved and sustained compliance rates. Resolute focus, audit, and feedback moved our center from a low- to high-performing center for timely venous thromboembolism prophylaxis.